The effect of pH and biomass concentration on lead (Pb) adsorption by Saccharomyces cerevisiae from simulated waste water - Mohd. Kamirul Nizam, Ngah@Omar (2006)
The contamination of wastewaters, river sediments and soil with toxic metals, is a complex problem. The removal of these contaminations has received much attention in recent years using conventional methods such as chemical reduction, ion exchange, and electrochemical treatment. The alternative method is discovered which is biosorption, refers to a physic-chemical binding of metal ions to biomass. The biosorption rate largely depends on parameters such as pH, initial biomass concentration and temperature. The biosorption of lead (Pb2+) from simulated waste water using baker’s yeast biomass is investigated. In this study, biosorption process was carried out in a shake flask at different initial pH and biomass concerntration. Results from experiment at different initial pH show that the percent of biosorption was highest at pH 4.0, i.e. 18.884 %. For the experiment conducted at different initial biomass concentration, the highest percent of biosorption was obtained by using 2.5 mg/l of biomass. From the results also, it was observed that percent of biosorption is directly proportional to the biomass concentration.